2008
DOI: 10.1002/ps.1637
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of the herbicide sulcotrione: formation of a major photoproduct and its toxicity evaluation

Abstract: On irradiation, sulcotrione mainly gives the photocyclization product, which presents a higher toxicity than sulcotrione and CMBA. This cyclization product should thus be considered in sulcotrione environmental risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Although SUL degradation products had no herbicide activity, they present toxicity towards unicellular organisms different of sulcotrione toxicity (Ter Halle et al 2009; Wiszniowski et al 2009). According to Goujon et al (2014), SUL possesses genotoxic properties against Allium cepa L. The detailed physicochemical parameters of all above-mentioned herbicides and their degradation products are placed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Although SUL degradation products had no herbicide activity, they present toxicity towards unicellular organisms different of sulcotrione toxicity (Ter Halle et al 2009; Wiszniowski et al 2009). According to Goujon et al (2014), SUL possesses genotoxic properties against Allium cepa L. The detailed physicochemical parameters of all above-mentioned herbicides and their degradation products are placed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that photolytic degradation of triketone herbicides substituted by a Cl atom, such as sulcotrione and tembotrione, mainly resulted in efficient formation of a xanthenic derivative by intramolecular photocyclization in acidic form. , Irradiation time and rising photoproduct levels clearly increased the toxicity of the mixture toward tested organisms (V. fischeri and A. cepa ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…80 The cyclization photoproduct of sulcotrione is more toxic than the parent compound. 85 The ability of river water (2.9 mg C per L, 0 mg NO 3 À per L) to quench the photolysis of the herbicide was attributed to light screening. 80 In the same study, the ability of seawater (1.1 mg C per L, 0.02 mg NO 3 À per L) to accelerate sulcotrione photolysis was attributed to nitrate photolysis.…”
Section: Azole Fungicidesmentioning
confidence: 99%